Aktivitas Antioksidan dan Fotoproteksi Ekstrak Kasar Bakteri Berpigmen Asosiasi Gastropoda Cassidula nucleus - Marwa Irfan Hanif; Delianis Pringgenies; Wilis Ari Setyati (Jurnal Kelautan Tropis, 2025)
Excessive UV radiation generates free radicals, damaging healthy skin cells. Bioactive compounds with photoprotection and antioxidant properties offer a promising treatment for this damage. Pigments, often sourced from marine microbes associated with marine organisms, are natural materials known for these capabilities. This study aimed to identify antioxidant and photoprotection activities in pigmented bacteria linked to gastropods. A source of pigments is marine microbes associated with marine organisms. This study aims to determine the antioxidant and photoprotection activities of pigmented bacteria associated with the gastropod. Gastropod samples were obtained from the mangrove ecosystem of Mangkang Semarang and bacteria were isolated by the spread plate method. This research method is explorative descriptive, includes colony characterization, bacteria mass culture and maceration extraction of bacteria using methanol, carotenoid content calculation, antioxidant and photoprotection activity test, compound preliminary analysis using Fourier Transform Infrared spectroscopy (FTIR) and molecular identification of bacteria. The results obtained 2 bacterial isolates derived from the gastropod Cassidula nucleus have colored colonies. Based on the calculation of the highest carotenoid content is in the isolate with the code MK.CN.3 amounting to 23.81 µg/g. Antioxidant activity test results from isolate MK.CN.3 showed IC50 value of 461 ppm with weak category and photoprotection value with SPF of 6.57 with extra protection category. Based on the analysis of crude extract, the pigment is suspected to contain carotenoids such as astaxanthin and β-carotene. The results of molecular identification showed that isolate MK.CN.3 is a strain of Isoptericola chiayiensis.